Long‐term changes in the water quality of a deep temperate oligotrophic lake in response to catchment disturbance: evidence from sediment cores - Alfred Theodore N. K. Kpodonu; David P. Hamilton; Christopher H. Lusk; Adam Hartland; Daniel C. Laughlin; Piet Verburg (New Zealand Journal of Marine and Freshwater Research, 2019)
This study examined long‐term stability in water quality of Lake Okataina, North Island, New Zealand, inferred from sediments deposited from 1836 to 2009, during which time there was a pyroclastic volcanic eruption (Tarawera 1886) and successive introductions of invasive mammals. Multiple geochemical proxies were analysed stratigraphically for organic matter loading, primary productivity, redox potential and phosphorus retention capacity. Organic matter loading to the lake is mostly authochthonous (algae) although there was increased allochthonous (terrestrial) loading immediately after the Tarawera eruption. After 1920, there was a sustained increase in inorganic erosion flux. Primary productivity appeared to increase considerably about 1960, but has remained relatively unchanged more recently. Our results suggest that the lake could recover from the impact of the volcanic eruption within a few decades, but the introduction of mammals may affect its resilience and lead to more pervasive impacts on the biogeochemistry.